Relationship between modified Nutrition Risk in the Critically Ill (mNUTRIC) Score and nutrition intake with quadriceps femoris muscle thickness in critically ill patients - Mahendra Dwi Aditya Lopulalan; Prananda Surya Airlangga; Arie Utariani (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
Abstract  Muscle wasting in critical illness is seen from inadequate nutrition intake and stress catabolism. Modified Nutrition Risk in the Critically Ill (NUTRIC) Score is a screening tool that measures starvation, inflammation, disease severity, and organ dysfunction. Relationship between muscle strength and muscle thickness causes the evaluation of muscle thickness is quite relevant. This study aimed to analyze the relationship between modified NUTRIC score and nutrition with muscle wasting in critically ill patients. The study was conducted on 30 patients in the ICU Dr Soetomo Hospital Surabaya. Nutritional intake and thickness of the quadriceps femoris muscle were monitored for one week. There was a relationship between mNUTRIC score with quadriceps femoris muscle thickness on days 3rd, 5th, and 7th. In the comparison between the low risk group and the high-risk group, it was found that there was a significant difference in the change in the percentage of muscle thickness difference on the 3rd, 5th and 7th day observation. There is a relationship between protein debt with quadriceps femoris muscle thickness (p = 0.008) with a positive correlation with moderate correlation strength (r = 0.477) on day 7. In conclusion, the modified NUTRIC Score had a moderate relationship with quadriceps femoris muscle thickness in critical patients from day 3rd until day 7th. The calorie intake not had a relationship with quadriceps femoris muscle thickness. Protein intake had a moderate relationship with quadriceps femoris muscle thickness only on day 7th measurement in critical patients. Keywords             : Modified NUTRIC Score, Nutrition, Quadriceps Femoris muscleCorrespondence   :           mdr.lopulalan@gmail.com